Literature review: Study on the development of teaching modules for excretory system material in senior high schools - Maulidya, Nifi; Susetyarini, Eko; Wahyono, Poncojari (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
The excretory system material, with a high level of difficulty, causes students to be less able to understand the material well. For this reason, a teaching module is needed that can help teachers in delivering the material so that there is no misunderstanding in conveying the concept, and a teaching module is made that can attract students' attention. However, some teachers have difficulty making modules. The purpose of this literature review is to analyze papers that develop modules on the excretory system material so that teachers can more easily create teaching modules on the excretory system material that include abstract material. The articles reviewed are limited to research published in 2018-2024, which can be found on Google Scholar and Research Gate. The search results obtained 10 articles that reported the development of modules on the excretory system material in high school. This literature study provides a comprehensive analysis of the trend in the development of teaching modules on the excretory system material. It can encourage future researchers to further explore other aspects of the various teaching modules produced. The development of teaching modules from year to year has increased due to the development of digital or electronic modules. This indicates that educators are aware of the importance of developing teaching modules in delivering material and making it easier for students to learn independently.